Growing in Cities: An Urban Penalty for Wild Birds? A Study of Phenotypic Differences between Urban and Rural Great Tit Chicks (Parus major) - Biard, Clotilde; Brischoux, François; Meillère, Alizée; Michaud, Bruno; Nivière, Manon; Ruault, Stéphanie; Vaugoyeau, Marie; Angelier, Frédéric (Frontiers in Ecology and Evolution, 2017)
Urban sprawl is associated with deep and intense modifications of the natural habitats of wild vertebrates. Although many species are unable to cope with such an environment, a few species can be found in cities and can help us assessing the impact of urbanization on wildlife. Urban-related environmental modifications are multiple and some of them seem beneficial while others seem rather detrimental to wild vertebrates. Moreover, the impact of these modifications on wild vertebrates is likely to vary depending on the phase of the annual life-cycle. Therefore, it is challenging to get a comprehensive picture of the impact of urbanization on wild vertebrates. Overall, urbanization is usually associated with reduced breeding performances in wild birds, but the impact of urbanization on the phenotype and quality of developing offspring has been less studied. In this study, we specifically investigated the impact of urbanization on several proxies of individual quality in great tits (Parus major). We concomitantly measured body size (tarsus length and body mass), plumage coloration, and telomere length in 14-days old chicks issued from 4 populations (2 pairs of urban/rural populations located in two different geographical areas of France). First, rural chicks were significantly taller and heavier than urban birds although this impact of urbanization on body size/body mass appears only true for the most urbanized site. Interestingly, body size was also affected by the geographical area of capture, suggesting that regional environmental conditions may attenuate or exacerbate the influence of urbanization on nestling growth. Second, the carotenoid-based yellow plumage of rural nestlings was more colorful than that of urban birds, independently of the area of capture. This suggests that urban birds probably have a low-carotenoid diet relative to rural birds. Finally, telomere length did not differ between rural and urban chicks. These results suggest that urbanization probably imposes large developmental constraints in wild vertebrates and that this impact may primarily be related to constraining nutritional conditions.